2008
DOI: 10.1002/ar.20705
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature Regime Through Premetamorphic Ontogeny on Shape of the Chondrocranium in the American Toad, Anaxyrus americanus

Abstract: If one considers the substantial amount of information that exists about phenotypic plasticity in amphibians, it is surprising that few studies have examined abiotic factors that influence phenotype through ontogeny. Phenotypic change and stability of morphology are artifacts of organisms that bear significant relevance to evolution within and among taxonomic groups. Here, we examine development as a phenotypically plastic aspect of larval anurans. Fertilized eggs of the American Toad, Anaxyrus (5 Bufo) americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Yntema, ; Mahmoud, Hess & Klicka, ; Crastz, ; Greenbaum, ). Our results mirror those of previous studies of incubation effects on developmental phenology in amphibians (Jorgensen & Sheil, ; Sheil et al ., ). With our data, we can only speculate about the evolutionary causes of this thermally induced developmental plasticity.…”
Section: Discussionsupporting
confidence: 92%
“…Yntema, ; Mahmoud, Hess & Klicka, ; Crastz, ; Greenbaum, ). Our results mirror those of previous studies of incubation effects on developmental phenology in amphibians (Jorgensen & Sheil, ; Sheil et al ., ). With our data, we can only speculate about the evolutionary causes of this thermally induced developmental plasticity.…”
Section: Discussionsupporting
confidence: 92%
“…Morphometric studies of amphibian cranial variation typically focus on entire skulls or skull regions at pre-or postmetamorphic stages to address phylogenetic, functional or developmental questions (Emerson, 1985;Larson, 2002Larson, , 2004Larson, , 2005Larson, , 2008Jorgensen & Sheil, 2008;Ponssa & Candioti, 2012). This study in contrast focuses on the individual cartilages of a skull region throughout life, and separates their shape trajectories into phases of pre-and post-metamorphic growth and metamorphosis.…”
Section: The Evolutionary Significance Of the Lj And Ch Shape Trajectmentioning
confidence: 99%
“…Temperature is known to affect timing (Harkey and Semlitsch 1988) and size at metamorphosis (Bizer 1978), but few studies have documented how differences in temperature regimes can affect the sequence of ossification. Jorgensen and Sheil (2008) utilized geometric morphometrics to study shape change induced by different temperature regimes on Anaxyrus (i.e., Bufo) tadpoles and found that mean chondrocranial shape of those specimens raised under a regime of fluctuating daily temperatures most closely approximated the consensus shape of the overall dataset, perhaps suggesting that a fluctuating regime may be preferred for achieving shape changes in the lab that are like those of the wild condition. However, raising animals under constant temperatures may induce patterns of variation that are not representative of the natural condition.…”
Section: Source Of Specimens and Incubation Regime Through Developmentmentioning
confidence: 99%